Penyelesaian Konflik Pendirian Rumah Ibadah: Studi Kasus Konflik Gereja Methodist Kota Jambi - Riko Firdaus; Nurbaiti Nurbaiti; Abdul Halim; Zaki Mubarak (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2023)
This paper examines efforts to resolve conflicts over the establishment of houses of worship with a case study of the Methodist Church in Jambi City. This church has been sealed by the Jambi Mayor Government which is considered to have violated the regulations for the establishment of houses of worship in the Joint Regulation of the Minister of Religious Affairs and Minister of Home Affairs No. 8 and 9 of 2006. This paper uses field research methods with a sociological approach. Data collection techniques are carried out through observation, interviews, and documentation. Then the data is analyzed through data reduction, data presentation and verification conclusions. The results of this study found that the conflict occurred due to rejection from residents around the Methodist Church, and the establishment of a Church that did not meet the applicable licensing requirements. The initial settlement efforts carried out by the Regional Government are security and supervision, then mediation is carried out between the two parties, in this case the mediators who play an active role are Lurah, Sub-district, Kemenag, Kesbangpol, and FKUB Jambi City. The conflict of the Methodist Church did not lead to violence, and took place safely, the settlement was also carried out through mediation through the government and participated in the contribution of Jambi customs and culture.